2015
DOI: 10.1159/000435818
|View full text |Cite
|
Sign up to set email alerts
|

Higher Cardiovascular Risk in Common Variable Immunodeficiency and X-Linked Agammaglobulinaemia Patients

Abstract: Introduction: Common variable immunodeficiency and X-linked agammaglobulinaemia are primary immunodeficiencies classified as antibody deficiencies, and they both result in hypogammaglobulinaemia. Objective: Evaluate the lipid profile and other cardiovascular risk biomarkers in CVID and XLA patients. Methods: In total, 24 patients and 12 healthy controls matched by age and gender were included in the study. We evaluated anthropometric measurements, and seric total cholesterol (TC), high-density lipoprotein chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Other inflammation markers, SAA and ferritin concentrations, were also increased in the patients, but this increase was not statistically significant (P ¼ 0.110, P ¼ 0.716). Vieira et al 29 showed that CVID patients had presented themselves with increased inflammatory markers -CRP (P ¼ 0.008) and TNF-alpha (P < 0.001) concentrations were significantly higher.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other inflammation markers, SAA and ferritin concentrations, were also increased in the patients, but this increase was not statistically significant (P ¼ 0.110, P ¼ 0.716). Vieira et al 29 showed that CVID patients had presented themselves with increased inflammatory markers -CRP (P ¼ 0.008) and TNF-alpha (P < 0.001) concentrations were significantly higher.…”
Section: Discussionmentioning
confidence: 98%
“…Lipid profile changes are well-known risk factors for adult coronary artery diseases, but we can find only a few research works for CVID. Vieira et al 29 investigated the lipid profile and other cardiovascular risk biomarkers in CVID. HDL-cholesterol (P ¼ 0.025) and apolipoprotein A-I (P ¼ 0.013) concentrations were significantly lower in patients which can predispose to a high cardiovascular risk and there was a negative correlation between HDL-cholesterol and triglyceride (r ¼ À0.641; P ¼ 0.001) concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation parameters, such as TNF-alpha, CRP and IL-6 are also known to play an effective role in the pathogenesis of atherosclerosis which is a chronic disease. In addition, apo-A and high-density lipoprotein cholesterol levels and chronic inflammation were lower in this patient group (21). When evaluated with this evidence, atherosclerotic heart disease was considered to have started at an early stage in CVID patients and was thought to display a rapid course.…”
Section: Discussionmentioning
confidence: 86%
“…In CVID patients, the disease is usually diagnosed within about 8 years after first symptoms, and this diagnostic delay results in delayed initiation of standard treatments (immunoglobulin), thereby increasing (19). Although the life expectancy of CVID patients increases with improved treatment methods, the presence of chronic inflammation leads to the development of different diseases in this patient group (20,21). In CVID patients, TNFalpha and CRP levels were found to be higher as indicators of chronic inflammation compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation